Heterogeneity and spatial dependence in Okun's law: a global view - Ángel Maridue\~na-Larrea; Ángel Martín-Román; Sylvina Porras-Arena (Global Labor Organization (GLO), 2025)
This study analyses the relationship between unemployment and economic growth at the international level, addressing the nature and decomposition of the Okun coefficient. Using World Bank data from 173 countries between 1991 and 2019, econometric techniques including decompositions and spatial dependence analysis are applied. First, the validity of Okun's law is confirmed, noting the heterogeneity of the coefficient across countries, suggesting the need for context-specific approaches to improve labour dynamics. Second, the evidence underlines the importance of labour productivity over labour supply as a key determinant of the unemployment-output relationship. Finally, the identification of spatial patterns highlights the interdependence between neighbouring economies, justifying coordinated strategies at the regional level to boost employment. These results provide valuable guidelines for the design of more effective public policies, adapted to the productive and labour realities of each country and capable of exploiting of the synergies arising from economic integration.
Keywords: C21; C32; E32; J21; R23; 330; Okun's Law; Economic growth; Unemployment; Labour productivity; Labour supply; Spatial dependence; Economic integration